Spanish preferred argument structure across time and space - Bentivoglio, Paola (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This study discusses whether a pragmatically motivated grammatical structure known as Prefered argument structure (PAS) was already present in Old Spanish. The Ancient Spanish corpus, consisting of 12th and 14th century literary documents, was analyzed according to the same procedures adopted in a study of Modern Spoken Spanish, confirming the initial hypothesis that no relevant changes occurred in this particular discursive structure.